Access and inclusion policies for visually impaired students in education in Mozambique (Research, Society and Development, 2023)
This research aims to describe access and inclusion policies for students with visual impairments in education in Mozambique. To achieve this objective, a bibliographic review study was carried out based on scientific publications and normative documents from the Government of Mozambique (GM) from 2016 to 2023, as well as organizations that support Education at National and International Level. The reflections presented, based on evidence from the literature on the subject, give us the understanding that inclusive education policies in Mozambique present a practical deficit in their application, that is, legislation and laws claim the right to inclusive education for the visually impaired. , but its application has had flaws that often arise from the lack of qualified teachers, inadequate school facilities and a shortage of teaching materials that meet the educational needs of students with visual impairments. Furthermore, there is weak supervision and regulation of responsible bodies across the country, which makes it difficult to fulfill the fundamental right to education for students with special educational needs. Inclusive education in the country is carried out in a segregated manner, giving the feeling of discrimination in the school environment, which can somehow contribute to school dropout rates. The inclusive education policies in use in the country are not efficient, because they do not address the heterogeneity of students. Therefore, we can state that for the concrete implementation of inclusion, it is necessary to adapt current policies to the local reality.